The effect of increased strength on ball release speed and front foot contact-phase technique in elite male cricket fast bowlers - Felton, P. J.; Shine, K. J.; Yeadon, M. R.; King, M. A. (Journal of Sports Sciences, 2025)
Research on strength in cricket fast bowling has focused on ball release speed over technique. This study investigates how increased strength affects performance and front foot contact-phase technique during fast bowling. A planar, 16-segment, whole-body torque-driven simulation model, customised and evaluated for 10 elite male fast bowlers, was used to optimise the technique for maximum ball release speed under 3 conditions: 1) original strength; 2) 5% increased lower body strength and 3) 5% increased lower body + shoulder strength. As strength increased across conditions, discrete and continuous one-way ANOVA`s with post-hoc t-tests, highlighted ball release speed increased (40.7 vs 41.3 vs 41.5 ms-1; p < 0.01), vertical front foot ground reaction impulse decreased (p < 0.023) and mid-phase bowling shoulder extensor torque increased (53% to 61%; p < 0.05). No significant differences were found in phase time, ground reaction forces, joint kinematics or joint kinetics, although the increased strength techniques exhibited less knee extension, reduced trunk flexion and greater shoulder extension, contrary to expectations. This suggests that increased strength may lead to alterations in the front foot contact technique which allows greater muscular momentum to be generated. Caution is advised when considering using strength interventions to alter the front foot contact-phase technique.